The returns to undergraduate degrees by socio-economic group and ethnicity - Jack Britton; Lorraine Dearden; Ben Waltmann (Institute for Fiscal Studies (IFS), 2021)
We investigate differences in the returns to undergraduate degrees by socio-economic background and ethnicity using the Department for Education's Longitudinal Education Outcomes (LEO) data set. The LEO data set links school records, university records and tax records for everyone who took GCSEs in England since 2002. Using these data, we can estimate returns up to age 30.
Keywords: 330; Bildungsertrag; Akademiker; Ethnische Gruppe; Soziale Schicht; Großbritannien